IMPLEMENTATION OF IJARAH MUNTAHIYAH BITTAMLIK ACADEMIC BASED ON ISLAMIC LAW AND ISLAMIC BUSINESS ETHICS - Rachman, Muchammad Arif; Kholidah, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Ijarah Muntahiyah Bittamlik (IMBT)  contract is one of the new contracts in the world of Islamic finance, especially at the SMNU KSPPS. The Ijarah Muntahiyah Bittamlik (IMBT) is part of the Islamic banking sector. This study aims to describe the implementation of the Ijarah Muntahiyah Bittamlik (IMBT)  contract at KSPPS SMNU Bojong Pekalongan Branch, and review Islamic law and Islamic business ethics towards the implementation of the Ijarah Muntahiyah Bittamlik (IMBT) contract at KSPPS SMNU Bojong Pekalongan Branch. This study uses a qualitative approach, with a type of field research. The data collection techniques used interviews, documentation, and literature studies, while the data validity testing techniques used the credibility method and the triangulation method. The data analysis technique used is descriptive qualitative analysis. The result of this study is the implementation of the Ijarah Muntahiyah Bittamlik (IMBT)  contract at the KSPPS SMNU Bojong Pekalongan branch based on Islamic law and Islamic business ethics. In the research review of Islamic law, the researcher found that it was in accordance with existing Islamic law, such as the Koran, hadith, fiqh rules, ijma' ulama, Fatwa of the Syari'ah Council No.27/DSN-MUI/III/2002, and PSAK No. 107 (Ijarah Accounting). As for the Islamic business ethics, it is in accordance with the ethics of honesty (honesty), determination (reliability), loyalty, and discipline.